Ergot Use and Overuse: A Pharmacoepidemiology Retrospective Cohort Study. Issue 3 (March 2016) - Donnet, A.; Braunstein, D.; Pradel, V.; Sciortino, V.; Allaria‐Lapierre, V.; Micallef, J.; Lanteri‐Minet, M.
Abstract : Objective: The objective of this study was to estimate and to characterize the actual patterns of ergot use and overuse in France using a drug reimbursement database. Methods: We included all people covered by the French General Health Insurance System (GHIS) from the Provence‐Alpes‐Côte‐d'Azur (PACA) and Corsica administrative areas who had at least one prescription of ergot between May 2010 and December 2011. All prescriptions of ergots, migraine prophylactic treatment, and psychotropic medications were extracted from the GHIS database. We defined occasional ergot users (<3 months of prescription) and regular ergot users (>3 months of prescription). Among regular ergot users, we identified overusers and nonoverusers. Results: We included 4358 patients who had at least one prescription of ergots (oral ergotamine tartrate, dihydroergotamine mesilate nasal spray, intravenous dihydroergotamine mesilate). Among ergot overusers, a large majority of patients had ergotamine tartrate overuse. The proportion of ergotamine tartrate overusers is maximum after 55 years. Compared with regular users, overusers use more frequently a prophylactic treatment (93/165 [56.4%] versus 398/1057, OR = 2.15, P  < .001), antidepressants (72/165 [43.6%] versus 326/1057 [30.8%] OR = 1.79, P  < .001), benzodiazepines (111/165 [67.3%] versus 613/1057 [58.0%], OR = 1.50, P  < .001), weak opioids (95/165 [57.6%] versus 463/1057 [43.8], OR = 1.77, P  < .001) and strong opioids (13/165 [7.9%] versus 24/1057 [2.3%], OR = 3.86, P  < .001). The coexistence of ergot consumption and triptan overuse, and the possibility of both triptan and ergot overuse was described; triptan overusers were more described in ergotamine overusers than in nonoverusers. Conclusions: This work outlines a high prevalence of ergotamine tartrate overuse (11.1%). As ergotamine tartrate users are mostly aged more than 55 years, an evaluation of ergotamine cardiovascular risk profile is necessary in the elderly population.